Standard system for the evaluation of bean germplasm - Schoonhoven, Aart van; Pastor Corrales, Marcial A. (International Center for Tropical Agriculture, 1987)
A standard system for the evaluation of bean germplasm under field conditions is described, including a table with the developmental stages of the common bean plant which is used in the proposed system. This system has been tested in Colombia and many countries in Latin America, Africa, and other regions. Such evaluation system considers the following measurements: general agronomic characteristics (seed color, size, and brilliance; growth habit; days to flowering and maturity; vegetative and reproductive adaptation; nodulation), damage caused by diseases (viral, fungal, and bacterial), nematodes, and arthropods (bean flies, aphids, red and white spider mites, leafhoppers and leaf feeders, bean pod weevils, and bruchids), and tolerance to soil and climatic factors (drought and acid soils). Each one of the above mentioned measurements is explained in detail. (CIAT)